Prospective and Longitudinal Analysis of Lymphocyte Subpopulations in SARS-CoV-2 Positive and Negative Pneumonia: Potential Role of Decreased Naïve CD8+ in COVID-19 Patients - Makhabbat Bekbossynova; Lyudmila Akhmaltdinova; Kuanysh Dossybayeva; Ainur Tauekelova; Zauresh Smagulova; Tatyana Tsechoeva; Gulsimzhan Turebayeva; Aliya Sailybayeva; Zhanar Kalila; Takhmina Mirashirova; Timur Muratov; Dimitri Poddighe (Viruses)
Background: During the acute phase of COVID-19, a number of immunological abnormalities have been reported, but few studies longitudinally analyzed the specific subsets of peripheral blood lymphocytes. Methods: In this observational, prospective, and longitudinal study, adult patients developing acute pneumonia during the COVID-19 pandemic have been followed up for 12 months. Peripheral blood lymphocyte subsets were assessed (with a specific focus on the memory markers) at 6 time points after the disease onset until 12 months. Results: A total of 76 patients with acute pneumonia (characterized by a prevalently interstitial pattern of lung inflammation) at the hospital admission (who completed the 12-month follow-up period) were recruited in this study. They were divided into two groups, namely positive (n = 31) and negative (n = 45) patients for the SARS-CoV-2 PCR test. In the acute phase, the general lymphocyte immunophenotyping profile was comparable for most parameters between these groups, except for B cells. When B and T cells were analyzed according to the expression of memory markers, a significant decrease in naïve CD8+ T cells was observed in the SARS-CoV-2-positive pneumonia group during the acute phase. Notably, this aspect was maintained during the follow-up period for at least 9 months. Conclusions: COVID-19 pneumonia seems to be associated with a lower number of naïve CD8+ T cells compared to pneumonia patients negative for this virus. This alteration can persist in the convalescent phase.